Musical activities between father and toddler in local music centre in Klang Valley / Kang Yee Farn - Kang , Yee Farn (2020)
Historically, different forms of musical activities, including singing, was one of the earliest ways of parents to bond with their children. Lullaby or other forms of singing has been used for ages to encourage or teach children necessary skills required in future. As recent studies signify, the effects of the music education from the early ages can have very positive effects on the children. Meanwhile, by growing the popularity of musical early childhood programs the number of researches on outcome of these classes are increasing. However, there are not many researches in which the focus specifically aim the effects of such courses on the emotional bonding between children and their fathers. Due to the modern life style, busy schedule, and the main role of the fathers as the provider for family, the number of mothers who attending the classes with their children are more than the fathers. Therefore, observing fathers who continuously attend the musical activity classes with their children can be much harder task for the researcher. Nevertheless, this matter should not be an obstacle to prevent researching the effects of the music and movement courses on the paternal bonding. This research contributes to raise the awareness of both fathers and the educators of the musical activity courses about the effects of the music and movement courses for children between 11 to 30 months on the paternal bonding. This research looks forward to help fathers to understand that what are the positive effects of musical activities on their emotional connections with their children. Furthermore, this research can be a reference for educators and course designers to gain a better insight of fathers standpoints about these current activities and what they believe is the most helpful part of these courses.